Haemophilia A mutations in patients with non-severe phenotype associated with a discrepancy between one-stage and chromogenic factor VIII activity assays - Pavlova, Anna; Delev, Daniel; Pezeshkpoor, Behnaz; Müller, Jens; Oldenburg, Johannes (Thrombosis and Haemostasis, 2014)
About one-third of patients with non-severe haemophilia A (HA) show a discrepancy of factor (F)VIII activity (FVIII:C) measured by one-stage (FVIII:C1st), two-stage assays or the chromogenic method (FVIII:Cchr). The aim of the study was to characterise the mutation profile in patients with FVIII:C assay discrepancies. FVIII:C discrepancy was considered significant if the calculated ratio between FVIII:C1st and FVIII:Cchr was ≤ 0.6. In 16 patients FVIII:C1st was higher than FVIII:Cchr. The reverse phenomenon was observed in 83 patients. Genetic analysis revealed 23 different missense mutations of which 17 were novel. Most mutations, exhibiting a higher FVIII:C1st were localised in the A1-A2-A3 interface. The majority of mutations associated with FVIII:Cchr>FVIII:C1st discrepancy were located close to or within the thrombin cleavage sites, FIX or vWF binding sites. Our data show a correlation between FVIII:C and thrombin generation testing with a clear differentiation between patients with haemophilia and normal controls. However, in the subgroup of FVIII:C1st>FVIII:Cchr discrepancy, the endogenous thrombin potential and peak thrombin parameters were similar to non-discrepant haemophilia patients, while in the inverse discrepancy FVIII:Cchr>FVIII:C1st, these variables showed values close to that of the normal control group. Certain hereditary F8 mis-sense mutations cause discrepancy in FVIII:C as measured with different assays. This can lead to failure in diagnosing HA or incorrectly classifying the severity of the disease. Therefore, we recommend that initial diagnosis of non-severe HA phenotypes should be based on results of both FVIII:C1st and FVIII:Cchr assays.
Keywords: Haemophilia A; discrepant assay; missense mutations